2020
DOI: 10.1101/2020.04.10.996116
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Head-mounted microendoscopic calcium imaging in dorsal premotor cortex of behaving rhesus macaque

Abstract: HighlightsFirst demonstration of head-mounted microendoscopic calcium imaging in behaving macaque.Surgical protocols developed for preparing the animal for calcium imaging, including virus injections to express GCaMP and chronic implantation of a GRIN lens to enable optical access to gyral cortex.Proof of concept plug-and-play calcium imaging in behaving macaques with months long stable recording capability allowing populations of individual neurons to be tracked longitudinally.Bilateral calcium imaging from d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 77 publications
0
11
0
Order By: Relevance
“…Imaging from the surface, Trautmann et al found similarly heterogeneous tuning among neuronal somata and processes. Together, this pair of studies provides complementary insights into the organization of movement representation across the cortical sheet (Trautmann et al, 2021) and across layers (Bollimunta et al, 2021). These data contribute to continued debate about the spatial organization of motor cortex (Omrani et al, 2017), which calcium imaging can resolve more decisively than electrophysiology.…”
mentioning
confidence: 89%
See 4 more Smart Citations
“…Imaging from the surface, Trautmann et al found similarly heterogeneous tuning among neuronal somata and processes. Together, this pair of studies provides complementary insights into the organization of movement representation across the cortical sheet (Trautmann et al, 2021) and across layers (Bollimunta et al, 2021). These data contribute to continued debate about the spatial organization of motor cortex (Omrani et al, 2017), which calcium imaging can resolve more decisively than electrophysiology.…”
mentioning
confidence: 89%
“…Nevertheless, these studies mark an exciting foray into the use of calcium imaging in behaving macaques, and they chart a course to new discoveries into the neural mechanisms of movement and cognition. B) The miniscope system of Bollimunta et al (2021) consists of a miniature endoscope (black and gray), silicone elastomer (blue), aluminum cylinder (black), and cement/acrylic (green).…”
Section: Llmentioning
confidence: 99%
See 3 more Smart Citations